Distribution and ecology of the groupers (Serranidae) and snappers(Lutjanidae) of the Netherlands Antilles - Nagelkerken, W.P. (Amsterdam Scientific Research in Surinam and the Netherlands Antilles, 1981)
Publications of the Foundation for Scientific Research in Surinam and the Netherlands Antilles ; no. 107
Keywords: Netherlands Antilles; Snappers; Groupers